Kombinasi pengemasan vakum dan iradiasi untuk memperpanjang masa simpan ikan kayu (Keumamah) - Abdul Hadi; Iskandar Iskandar; Wiqayatun Khazanah; Median Rolando (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
Keumamah, or dried fish, is one of Aceh Province's traditional delicacies whose ingredient is mackerel tuna. The making of dried fish (Keumamah) is a method of preserving fish to prolong its shelf life. The study aimed to measure the storage time of dried fish (Keumamah) using vacuum packaging and irradiation. The study used an experimental design through the Randomized Control Trial (RCT) method. Statistically analyzed using ANOVA and advanced Duncan test with Confidence Interval (CI) of 95%. This study showed that vacuum irradiation could significantly preserve the colour, taste, flavour, and texture characteristics of the dried fish (p < 0,01) for all variables. The Total Plate Count (TPC) test and water, protein, and fat content analysis suggest a significantly better post-storage condition of the dried fish using a vacuum and irradiation combination. Meanwhile, the analysis of ash content did not show a significant difference between treatment and control groups (p= 0,386). In conclusion, the packaging with a combination of vacuum and irradiation could prolong the shelf life of dried fish